CLINICAL CASE HISTORY OF EPTIFIBATIDE USE DURING CORONARY INTERVENTION IN PATIENT WITH CORONARY FAILURE - K. A. Kireev; A. V. Krasnopeev; T. S. Kireeva (Рациональная фармакотерапия в кардиологии)
Clinical case history of endovascular intervention in infarct related coronary artery with 4 sirolimus-eluting stents implantation and their further thrombosis during early postoperative period is described. Percutaneous coronary intervention was successful after the balanced medication with 2 antiplatelet drugs (acetylsalicylic acid and clopidogrel) and heparin. There were not any reasons for additional prescription of antiplatelet medicine. It seems that one of the main reasons of the stent thrombosis was the extended area of 4 sirolimus-eluting stents implantation into the affected vessel. After the analysis of our clinical case history we propose that for stent thrombosis prevention in multistent (≥4 drugeluting stents) interventions it is necessary to apply additional antiplatelet drug – glycoprotein IIb/IIIa inhibitor eptifibatide.